Translation of The Otago Exercise Program for Adoption and Implementation in the United States - Shubert, Tiffany E.; Smith, Matthew Lee; Ory, Marcia G.; Clarke, Cristine B.; Bomberger, Stephanie A.; Roberts, Ellen; Busby-Whitehead, Jan (Frontiers in Public Health, 2015)
.